A plastically bendable and polar organic crystal. Issue 33 (30th July 2021) - Kusumoto, Sotaro; Sugimoto, Akira; Kosumi, Daisuke; Kim, Yang; Sekine, Yoshihiro; Nakamura, Masaaki; Hayami, Shinya
Abstract : An organic crystal of the polar space group Pc that is capable of plastic bending is reported, and its high dielectric constant and strong second-order harmonic generation (SHG) effect have been demonstrated. Abstract : In this communication, an organic crystal of the polar space group Pc that is capable of plastic bending in response to external mechanical stress is reported, and its high dielectric constant and strong second-order harmonic generation (SHG) effect have been demonstrated.